A Commentary on the United Nations Convention on the Rights of the Child, 24 : the Right to Health. - Eide, Wenche Barth (BRILL, 2006)
Part of "A Commentary on the United Nations Convention on the Rights of the Child" series, this work presents a commentary on Article 24. The series is sponsored by the Belgian Federal Science Policy Office.